2021
DOI: 10.1186/s12889-021-10226-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the municipal human development index and maternal education on infant mortality: an investigation in a retrospective cohort study in the extreme south of Brazil

Abstract: Background Infant mortality is considered an important and sensitive health indicator in several countries, especially in underdeveloped and developing countries. Most of the factors influencing infant mortality are interrelated and are the result of social issues. Therefore, this study performed an investigation of the influence of the MHDI and maternal education on infant mortality in a capital in the extreme south of Brazil. Methods It is a retr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
(48 reference statements)
3
9
0
6
Order By: Relevance
“…Low maternal education is consistently cited as a risk factor for complications in pregnancy and lower adherence to recommendations and is usually related to worse socioeconomic conditions [13,14,27,42]. In this study, we observed an association of CA with lower education only in very high development regions (RR 1.27 95% CI 1.03-1.54), suggesting that the mother's individual choices, such as better adherence to recommendations, may outweigh the exposure of the socioeconomic environment in which she lives.…”
Section: Discussionmentioning
confidence: 99%
“…Low maternal education is consistently cited as a risk factor for complications in pregnancy and lower adherence to recommendations and is usually related to worse socioeconomic conditions [13,14,27,42]. In this study, we observed an association of CA with lower education only in very high development regions (RR 1.27 95% CI 1.03-1.54), suggesting that the mother's individual choices, such as better adherence to recommendations, may outweigh the exposure of the socioeconomic environment in which she lives.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the municipal human development index and maternal education on infant mortality: an investigation in a retrospective cohort study in the extreme south of Brazil (59) 2021/Brasil Estudo de coorte/ n=3.107…”
Section: / Argéliamentioning
confidence: 99%
“…• A baixa escolaridade materna está associada a maior taxa de mortalidade infantil (2)(3)(4)(5)(6)(7)(8)11,(21)(22)(23)(25)(26)(27)32,33,35,(41)(42)(43)(44)(45)49,52,54,(58)(59)(60)(62)(63)(64)(65) , a alta taxa de mortalidade infantil (3,19,36,49,(55)(56)(57) , a mortalidade evitável no primeiro dia (30) e a mortalidade infantil prematura em unidade terapia intensiva neonatal (16) .…”
Section: Aspectos Relacionados àS Características Maternasunclassified
See 1 more Smart Citation
“…In Brazil, several studies provide evidence of higher mortality rates in more impoverished areas 9 . Many are the composite socioeconomic measures available at the municipal level, such as the Social Vulnerability Index ( Índice de Vulnerabilidade Social – IVS) 12 , and the Municipal Human Development Index (MHDI) 13 – still, mortality rates can be highly heterogeneous 14 , making more disaggregated analyses desirable.…”
Section: Introductionmentioning
confidence: 99%